2010
DOI: 10.1002/cphc.200901029
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory behaviour in Galvanostatic Formaldehyde Oxidation on Nanostructured Pt/Glassy Carbon Model Electrodes

Abstract: The electrocatalytic oxidation of formaldehyde, which results in CO(2) and HCOOH formation, was investigated under galvanostatic conditions on nanostructured Pt/glassy carbon (GC) electrodes fabricated by employing colloidal lithography (CL). The measurements were performed on structurally well-defined model electrodes of different Pt surface coverages under different applied currents (current densities) and at constant electrolyte transport in a thin-layer flow cell connected to a differential electrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 72 publications
(104 reference statements)
0
18
2
2
Order By: Relevance
“…For the oxidation of formaldehyde, Miki et al 12 have proposed adsorbed bridge-bonded formate. Seidel et al 13 have shown that formic acid is produced in the direct path.…”
Section: Introductionmentioning
confidence: 99%
“…For the oxidation of formaldehyde, Miki et al 12 have proposed adsorbed bridge-bonded formate. Seidel et al 13 have shown that formic acid is produced in the direct path.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of . Reprinted from [19], Copyright 1995, with permission from Elsevier both Cl À and Br À is strongest for Pt(100), less pronounced for Pt (111), and weakest for Pt(110)-so weak that the oscillations were not detected. This sequence correlates with the oscillations which are only observed if anions adsorb so strongly that they lead to a decrease of the H 2 -oxidation current in the Cu-upd region in the Cu-free solutions.…”
Section: Oscillations In Anodic Oxidation Of Molecular Hydrogenmentioning
confidence: 89%
“…In very recent studies of the formaldehyde oxidation, Seidel, Krischer et al [111] have applied the nanostructured Pt/glassy carbon model electrode. In other words, the electrode consisted of catalytically active Pt nanodisks supported onto a planar glassy carbon substrate (Fig.…”
Section: Oscillatory Oxidation Of Formaldehydementioning
confidence: 99%
See 1 more Smart Citation
“…[35,36,40,41] In these reactions, an increaseoft he Pt loading or the Pt nanodisk coverageo nt he glassy carbon substrate, or alternatively,adecrease of the flow rate, was found to result in ah igher CO 2 current efficiency. This was explainedb ya ni ncreasingp robability of re-adsorptiona nd furthero xidation of the incompletely oxidized reactioni ntermediates to the completely oxidized and stable product CO 2 .…”
Section: à2mentioning
confidence: 97%